New Permutation Generation Under Exchange Strategy (PGuES) - Karim, Sharmila; Ibrahim, Haslinda; Omar, Zurni; Ahmad, Nazihah (Canadian Center of Science and Education, 2013)
An exchange based technique for generating permutation is presented in this paper.This strategy involved exchanging two consecutive elements, to generate the starter sets.For list all permutations, the exchange and reversing operations will be employed on these starter sets.The numerical result shows that new method is better than other existing methods.